Family Therapy and Cognitive Behavioral Therapy for a Case with Co-morbidity of Depression and General Anxiety Disorder in Hong Kong - A Single Case Study - Hiu-ying , Lau (International Journal of Psychosocial Rehabilitation, 2017)
Family therapy, a type of psychotherapy, is commonly applied in families having gridlocks, conflicts or misunderstandings, aiming at improving family functioning. The goals of family therapy include improving communication among family members, improving autonomy for each member, improve agreement about roles, reducing conflicts and reducing stress in the member who is the patient. (Gelder, Harrison & Cowen, 2006) In Virgina Satir’s model, congruence is an essence in achieving good communication between family members. Congruence refers to a state of being as well as a quality of communicating. It is viewed at three different levels. First, congruence entails acknowledging and accepting our inner experiences (sensations, interpretations, and consequent feelings about those feelings) and being able to express them. In the second level, it involves listening to our perceptions and expectations, and translating those into a responsible pattern of meeting our needs by tapping our yearnings. At level three, we move into harmony with spiritual essence, or what Satir called the universal life force. (Satir, Banmen, Gerber & Gomori, 1991)